2011
DOI: 10.1111/j.1399-5618.2011.00900.x
|View full text |Cite
|
Sign up to set email alerts
|

Criminal conviction, impulsivity, and course of illness in bipolar disorder

Abstract: Objective Criminal behavior in bipolar disorder may be related to substance use disorders, personality disorders, or other comorbidities potentially related to impulsivity. We investigated relationships among impulsivity, antisocial personality disorder (ASPD) or borderline personality disorder symptoms, substance use disorder, course of illness, and history of criminal behavior in bipolar disorder. Methods A total of 112 subjects with bipolar disorder were recruited from the community. Diagnosis was by Stru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 57 publications
2
26
0
1
Order By: Relevance
“…Clinical studies have demonstrated that impulsivity and risk-taking behaviours are stronger in bipolar disorder than in schizophrenia (30) and the rates of aggression and violence tend to be more pronounced in patients diagnosed with bipolar disorder who exhibit higher rates of impulsivity (31). Second, it has also been established that the risk of aggression in bipolar disorder increases substantially during acute manic episodes (31, 32), which are characterised by elevated levels of irritability, impatience and impaired insight (33). Genetically informative longitudinal clinical studies are therefore warranted to further explore the ways in which symptoms of mania interplay with substance misuse to generate increased levels of aggression and violence.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical studies have demonstrated that impulsivity and risk-taking behaviours are stronger in bipolar disorder than in schizophrenia (30) and the rates of aggression and violence tend to be more pronounced in patients diagnosed with bipolar disorder who exhibit higher rates of impulsivity (31). Second, it has also been established that the risk of aggression in bipolar disorder increases substantially during acute manic episodes (31, 32), which are characterised by elevated levels of irritability, impatience and impaired insight (33). Genetically informative longitudinal clinical studies are therefore warranted to further explore the ways in which symptoms of mania interplay with substance misuse to generate increased levels of aggression and violence.…”
Section: Discussionmentioning
confidence: 99%
“…Esses comportamentos envolvem tanto aspectos sutis de falta de reciprocidade nas interações interpessoais quanto comportamentos de natureza agressiva, sendo explicados por múltiplas trajetórias desenvolvimentais (Frick e Viding, 2009). Comportamentos socialmente desviantes são comuns a diversas condições psicopatológicas; por exemplo, ocupam um papel central no Transtorno da Personalidade Antissocial (American Psychiatric Association, 2013), e são também correlatos de traços de psicopatia (Cooke, Michie, Hart e Clark, 2004), e de Transtorno da Personalidade Borderline (Chabrol, Valls, Leeuwen e Bui, 2012), Transtorno da Personalidade Narcisista (Reidy, Zeichner, Foster e Martinez, 2008), e Transtorno Bipolar (Swann et al, 2011), além de outras categorias nosográficas. De um ponto de vista neurobiológico, comportamentos antissociais, especialmente aqueles agressivos, são influenciados por uma baixa ativação das estruturas cerebrais frontais (e.g., orbitofrontal) e das amígdalas (Blair, 2004), bem como por uma alta razão testosterona/cortisol (Terburg, Morgan e Van Honk, 2009).…”
Section: Análisis De Teoría De Respuesta Al íTem De Un Instrumento Brunclassified
“…Gender has no effect on impulsivity [5,28] or conviction history in bipolar disorder [36]. Approximately 90% of individuals with ASPD are men, but half of those with comorbid ASPD and bipolar disorder were women [37].…”
Section: Impulsivity In Bipolar Disordermentioning
confidence: 99%
“…In a crime-registry study of subjects discharged from hospitalization for an affective disorder, propensity toward mania predicted subsequent conviction [109]. The number of manic episodes no longer contributed significantly to conviction history when ASPD symptoms and rapid-response impulsivity were taken into account [36]. …”
Section: Combination Of Bipolar Disorder and Aspdmentioning
confidence: 99%
See 1 more Smart Citation